2017
DOI: 10.1080/19401493.2017.1332687
|View full text |Cite
|
Sign up to set email alerts
|

Simulating use scenarios in hospitals using multi-agent narratives

Abstract: Anticipating building-related complexities ensuing from occupants' behaviour is a major challenge in architectural design. Conventional building performance simulation tools model occupancy in a highly aggregated form, abstracting away the impact of dynamic spatial and social factors on occupant behaviour. To address this issue, we propose a multi-agent system that accounts for these aspects in process-driven facilities, such as hospitals. The approach involves modelling 'narratives', rule-based scripts that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Recent work on narrative-based modeling (Schaumann et al , 2017) demonstrated a practical approach to simulating day-to-day occupancy scenarios in medical facilities while representing dynamic building–occupant interactions. This approach is centered on narratives: computer scripts that store a pre-defined set of activities that involve multiple types of actors and unfold across several spaces .…”
Section: Relevant Studies On Human Behavior Simulation In Architectural Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work on narrative-based modeling (Schaumann et al , 2017) demonstrated a practical approach to simulating day-to-day occupancy scenarios in medical facilities while representing dynamic building–occupant interactions. This approach is centered on narratives: computer scripts that store a pre-defined set of activities that involve multiple types of actors and unfold across several spaces .…”
Section: Relevant Studies On Human Behavior Simulation In Architectural Designmentioning
confidence: 99%
“…First, we identified human behavior patterns in existing internal medicine wards and abstract them with the help of hospital managers, so they can be applied to generic facilities of the same type (details in Section 4). We then modeled these patterns computationally using a narrative-based approach (Schaumann et al , 2017) and simulated them in the two different design options (details in Section 5). The simulation results have been analyzed with respect to representative KPIs of day-to-day activities in hospital buildings (details in Section 6)[1].…”
Section: Research Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have used crowd simulation techniques to simulate the movement of people in built environments to approximate buildingoccupant behaviors. Some approaches focus on day-to-day behavior of people in offices [Goldstein et al 2010], hospitals [Schaumann et al 2017], and universities [Shen et al 2012]).…”
Section: Simulating Human-building Interactionsmentioning
confidence: 99%
“…Several approaches have been proposed to represent specific aspects of human behavior in architectural design using a combination of static and dynamic analyses. Such approaches include pedestrian movement [Yan and Kalay 2004], emergency egress [Chu et al 2014;Pan et al 2007], occupant presence and actions to support energy analyses [Goldstein et al 2010], people movement in university buildings [Shen et al 2013], and collaborative medical procedures in hospitals [Schaumann et al 2017a]. Nonetheless, how static and dynamic human-related analysis tools are actually used in architectural design to support architects' decision-making is still a relatively under-studied topic.…”
Section: Using Human Behavior Analysis Tools In Architectural Designmentioning
confidence: 99%